Alleviation of Photoinhibition by Co-ordination of Chlororespiration and Cyclic Electron Flow Mediated by NDH under Heat Stressed Condition in Tobacco - Li, Qinghua; Yao, Zheng-Ju; Mi, Hualing (Frontiers in Plant Science, 2016)
With increase of temperature, Fo gradually rose in both WT and the mutant inactivated in the type-1 NAD(P)H dehydrogenase (NDH), a double mutant disrupted the genes of ndhJ and ndhK (∆ndhJK) or a triple mutant disrupted the genes of ndhC, ndhJ and ndhK (∆ndhCJK). The temperature threshold of Fo rise was about 3-5 C lower in the mutants than in WT, indicating ∆ndhJK and ∆ndhCJK were more sensitive to elevated temperature. The Fo rise after the threshold was slower and the reached maximal level was lower in the mutants than in WT, implying the chlororespiratory pathway was suppressed when NDH was inactivated. Meanwhile, the maximum quantum efficiency of photosystem II (PS II) (Fv/Fm) decreased to a similar extent below 50C in WT and mutants. However, the decline was sharper in WT when temperature rose above 55C, indicating a down regulation of PS II photochemical activity by the chlororespiraory pathway in response to elevated temperature. On the other hand, in the presence of n-propyl gallate, one of the inhibitors of plastid terminal oxidase (PTOX ), the less evident increase in Fo while the more decrease in Fv/Fm in ∆ndhCJK than in WT after incubation at 50C for 6h suggest the increased sensitivity to heat stress when both NDH and chlororespiratory pathways are suppressed. Moreover, the net photosynthetic rate and photo-efficiency decreased more significantly in ΔndhJK than in WT under the heat stressed conditions. Compared to the light-oxidation of P700, the difference in the dark-reduction of P700+ between WT and ndhJK disruptant was much less under the heat stressed conditions, implying significantly enhanced cyclic electron flow in light and the competition for electron from PQ between PTOX and photosystem I in the dark at elevated temperature. Heat-stimulated expression of both NdhK and PTOX significantly increased in WT, while the expression of PTOX was less in ΔndhJK than in WT. Meanwhile, the amount of active form of Rubisco activase decreased much more in the mutant. The results suggest that chlororespiration and cyclic electron flow mediated by NDH may coordinate to alleviate the over-reduction of stroma, thus to keep operation of CO2 assimilation at